Improving Soil Health of Commercial Vegetable Home Gardens through Conservation Agriculture in Cambodia - Channaty Ngang; Pao Srean; David R. Ader; Florent Tivet; Ricky M. Bates (AGRITROPICA : Journal of Agricultural Sciences, 2023)
Tillage systems are components of broad agricultural practices that affect soil properties and soil health. These changes include soil respiration, density, moisture, and pH. Conservation agriculture practices have the potential to improve soil health by reducing tillage. In agricultural production, there can be numerous approaches to achieving consistently high yields annually; however, this study specifically looked at conventional tillage and conservation agriculture systems. This study aimed to determine soil fauna biodiversity and soil health under conservation agriculture (CA) and conventional tillage (CT) management practices of vegetable production in Cambodia. Five CA and five CT plots were selected and included in this study. Fifty soil samples were collected from CA and CT plots for soil fauna measurement, and in-situ tests were made using Biofunctool© for soil health assessment. The results showed that the abundance of soil fauna and aggregation stability were greater in CA than in CT. Soil fauna biodiversity enhancement may provide better soil health for soil improvement by adapting farming management practices.